Current therapeutic approaches to diffuse grade II and III gliomas. (16th January 2018) - Picca, Alberto; Berzero, Giulia; Sanson, Marc
The 2016 WHO classification of Tumors of the Central Nervous System brought major conceptual and practical changes in the classification of diffuse gliomas, by combining molecular features and histology into 'integrated' diagnoses. In diffuse gliomas, molecular profiling has thus become essential for nosological purposes, as well as to plan adequate treatment strategies and identify patients susceptible of target therapy. WHO grade II (low grade) and grade III (anaplastic) diffuse gliomas form a heterogeneous group of neoplasms, also known as 'lower-grade gliomas', characterized by a wide range of malignant potential. Molecular profile accounts for this biological diversity, and provides an accurate prognostic stratification of tumors in this group. Treatment strategies in lower-grade gliomas are ultimately based on molecular profile and WHO grade, as well as on patient characteristics such as age and Karnofsky performance status. The purpose of this review is to summarize recent advances in the classification of grade II and III gliomas, synthesize current treatment schemes according to molecular profile and describe ongoing research and future perspectives for the use of target therapies.